Evaluation of nocturnal hypokinesia in Parkinson's disease using a novel patient/proxy questionnaire and correlations with objective monitoring. (April 2019) - Bhidayasiri, Roongroj; Phokaewvarangkul, Onanong; Sringean, Jirada; Martinez-Martin, Pablo; Anan, Chanawat; Kantachadvanich, Nitinan; Chaudhuri, K. Ray; Hattori, Nobutaka
Abstract: Background: Nocturnal hypokinesia is a decreased ability to perform sufficient axial rotation and/or trunk flexion to turn in or get out of bed. Currently, there are no validated questionnaires specifically to assess nocturnal hypokinesia in PD patients. Objective: To develop and validate a questionnaire to assess PD patients' problems associated with turning or getting out of bed. Methods: The nocturnal hypokinesia questionnaire (NHQ) consists of 10 items, completed independently by patients and their caregivers. For validation, 76 patient-caregiver pairs completed the questionnaire and validity, agreement levels, and internal consistency assessed. In addition, 76 healthy couples served as controls. The NHQ and Modified Parkinson's Disease Sleep Scale (PDSS-2) were compared and 25 random patients-caregiver pairs were also assessed with objective night-time monitoring. Results: Patient and caregiver scores showed a high level of agreement (Intra-class correlation: 0.84) with high internal consistency (KR-20 coefficient of 0.73 for patients and 0.69 for caregivers). No significant difference between the mean total NHQ scores as rated by patients and caregivers was observed. Mean NHQ scores from patients and caregivers were significantly higher than healthy controls ( p  < 0.001). Moderate correlations were found between the NHQ and PDSS-2 (r = 0.32, p  = 0.004), and with objective monitoring (Number of turns: r = −0.41, p  = 0.04, Degree of turn: r = −0.44, p  = 0.02). Conclusion: The NHQ is a reliable instrument to identify symptoms of nocturnal hypokinesia amongst PD patients. Strong patient-caregiver agreement supports the use of proxy evaluation by caregivers when patient's information is unobtainable. Highlights: There are no validated questionnaires to assess nocturnal hypokinesia in practice. Our objective is to develop and validate the questionnaire for nocturnal hypokinesia. The NHQ consists of 10 items, rated independently by patients and caregivers. Our study confirms the internal and external validity of the NHQ in PD patients. The NHQ is a reliable instrument to identify NH symptoms amongst PD patients.